Evaluation of anticandidal activities and phytochemical examination of extracts prepared from Vitex agnus-castus: a possible alternative in treating candidiasis infections - Fatima O. Al-Otibi; Ghaida I. Alrumaizan; Raedah I. Alharbi (BMC, 2022)
Abstract Background Candidiasis infection is associated with high morbidity and mortality. Fungicidal resistance of some commercially used fungicides ascended the need for a naturally effective alternative. The current study aimed to evaluate the fungicidal activity of Vitex agnus-castus extracts in vitro against some Candida species. Methods The bioactive compounds contained in the crude and alcoholic extracts were compared, and the antioxidant activity was tested, as well. The phytochemical analysis was carried out by Fourier Transform-Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GC/MS). The scavenger activity of the tested extracts was tested, as well. The anticandidal activity was tested to detect the effect of the tested extracts on the mycelial growth of Candida albicans, Candida krusei, Candida parapsilosis, Candia tropicalis, Candida famata, Candida rhodotorula, and Candida dublinesis. The minimum inhibitory concentrations were calculated for all reported activities. The Scanning Electron Microscopy (SEM) and the Transmission Electron Microscopy (TEM) were used to detect the morphological and ultrastructure response in some selected species. Results FTIR and GC/MS revealed the existence of different bioactive chemical groups such as polyphenols, fatty acids, terpenes, terpenoids, steroids, aldehydes, alcohols, and esters, phytol which is a diterpene. DPPH results confirmed the antioxidant activity of all extracts where the methanolic extract was the strongest scavenging substrate. All extracts showed strong inhibitory effects against different species at a concentration of 200 µg/ml (P < 0.001). SEM and TEM showed morphological and ultrastructure changes in C. famata. Conclusion The current study suggested a reliable antifungal activity of different extracts of Vitex agnus-castus against different Candida species and strains. However, further studies are required to confirm the safety of these extracts to be used in medical applications.